A Cloning-Free Method for CRISPR/Cas9-Mediated Genome Editing in Fission Yeast. Issue 6 (1st June 2018) - Zhang, Xiao-Ran; He, Jia-Bei; Wang, Yi-Zheng; Du, Li-Lin
Abstract: The CRISPR/Cas9 system, which relies on RNA‐guided DNA cleavage to induce site-specific DNA double-strand breaks, is a powerful tool for genome editing. This system has been successfully adapted for the fission yeast Schizosaccharomyces pombe by expressing Cas9 and the single-guide RNA (sgRNA) from a plasmid. In the procedures published to date, the cloning step that introduces a specific sgRNA target sequence into the plasmid is the most tedious and time-consuming. To increase the efficiency of applying the CRISPR/Cas9 system in fission yeast, we here developed a cloning-free procedure that uses gap repair in fission yeast cells to assemble two linear DNA fragments, a gapped Cas9-encoding plasmid and a PCR-amplified sgRNA insert, into a circular plasmid. Both fragments contain only a portion of the ura4 or bsdMX marker so that only the correctly assembled plasmid can confer uracil prototrophy or blasticidin resistance. We show that this gap-repair-based and cloning-free CRISPR/Cas9 procedure permits rapid and efficient point mutation knock-in, endogenous N-terminal tagging, and genomic sequence deletion in fission yeast.